Discharge Rehabilitation Measures Predict Activity Limitations in Patients With Stroke 6 Months After Inpatient Rehabilitation. (21st August 2022) - Minor, Maria; Jaywant, Abhishek; Toglia, Joan; Campo, Marc; O'Dell, Michael W.
Abstract : Supplemental digital content is available in the text. Abstract : Objective: The aim of this study was to identify rehabilitation measures at discharge from acute inpatient stroke rehabilitation that predict activity limitations at 6 mos postdischarge. Design: This is a retrospective analysis of a prospective, longitudinal, observational cohort study. It was conducted in an acute inpatient rehabilitation unit at an urban, academic medical center. Activity limitations in patients ( N = 141) with stroke of mild-moderate severity were assessed with the activity measure for post-acute care at inpatient stroke rehabilitation discharge and 6-mo follow-up. Rehabilitation measures at discharge were investigated as predictors for activity limitations at 6 mos. Results: Measures of balance (Berg Balance Scale), functional limitations in motor-based activities (functional independence measure–motor subscore), and motor impairment (motricity index), in addition to discharge activities measure for post-acute care scores, strongly predicted activity limitations in basic mobility and daily activities at 6 mos (51% and 41% variance explained, respectively). Functional limitations in cognition (functional independence measure–cognitive subscore) and executive function impairment (Trail Making Test–part B), in addition to the discharge activities measure for post-acute care score, modestly predicted limitations in cognitively based daily activities at 6 mos (12% of variance). Conclusions: Standardized rehabilitation measures at inpatient stroke rehabilitation discharge can predict future activity limitations, which may improve prediction of outcome post-stroke and aid in postdischarge treatment planning.